Pasteurella aerogenes as an Asymptomatic Bacteriuria Agent. (21st April 2017) - Alaygut, Demet; Engin, Aynur
ABSTRACT: 'Asymptomatic bacteriuria' (ASB) is isolation of a specified quantitative count of bacteria in an appropriately collected urine specimen obtained from a person without symptoms or signs referable to urinary infection. Catheterized specimens are less likely to be contaminated compared with voided specimens; therefore, positive cultures of catheterized specimens are more likely to reflect true bladder bacteriuria even with low colony counts. The common pathogens for ASB are Escherichia coli, Klebsiella and Streptococcus spp . Pasteurella spp. was not previously reported as an ASB agent. ASB is important for pregnant women, children, individuals with obstructive uropathy, chronic renal failure and neutropenia, before the urologic procedures and after renal transplantation. Treatment of ASB is required for above situations. We report an 11-year-old-girl with neurogenic bladder who made clean intermittent catheterization and had Pasteurella aerogenes as an ASB agent.